Studying kazakh versions of the legends about Edige - Ualiyev T.A.; Kushkumbayev A.K. (Золотоордынское обозрение)
This research aims to review and systematize archival and published Kazakh versions of the epic of “Edige” (Yedige) and compile a complete list of texts while including their structural and textual analysis. For the materials of the article, both published and unpublished handwritten Kazakh versions of the legend of “Yedige” have been used. The work also involves extensive data from Kazakh historiography of the study of the epic of Edige, mainly the works of folklorists, as well as information from literary and historical sources. Results and scientific novelty: A chronological review of the history of the epic of Edige in Kazakhstan has been conducted. An overview of all known variants and a comparative analysis of the main plots and motives of the epic have been made. Information is provided about folklore researchers and historical circumstances and conditions in which it was necessary to record and publish various versions of the epic in Kazakhstan. Prohibiting the study of the epic “Edige” had a negative impact not only on the field of Edige studies, but also on the study of the epic in Kazakhstan as a whole, limiting the scientific potential of researchers who were forced to avoid this topic. As a result, the topic of Edige and the Golden Horde remained outside the focus of Russian historical science for a long time, and many scientists began to build their careers focusing on mainstream topics of that period. Three main regions of literary traditions were identified that influenced the formation of Kazakh versions of the legend. Variants of the legend of Edige, especially poetic fragments, had a significant impact on the work of the Kazakh akyns, zhyrshy, and zhyrau.